2014
DOI: 10.1111/1440-1630.12144
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and its relationship with health and wellbeing: The threshold concept for occupational therapy

Abstract: A threshold concept that captures the essential nature of occupational therapy is likely to be (highly) troublesome in terms of a learner's acquisition of it. Rather than simplifying these learning 'jewels' educators are encouraged to sit with the discomfort that they and the learner may experience as the learner struggles to grasp them. Moreover, they should reshape their curricula to provoke such struggles if transformative learning is to be the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…Therefore, examining and discussing teaching practices and content to meet this shortcoming could be useful. This reinforces the work already completed in this area by educators in Australia such as Wilcock () and more recently Gustafsson, Molineux and Bennett () and Fortune and Kennedy‐Jones (). Repositioning occupation to be central in university curriculum is not only being examined in Australia, with educators from the United States also investigating and developing an increased focus on occupation in curricula (Hooper et al ., ).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, examining and discussing teaching practices and content to meet this shortcoming could be useful. This reinforces the work already completed in this area by educators in Australia such as Wilcock () and more recently Gustafsson, Molineux and Bennett () and Fortune and Kennedy‐Jones (). Repositioning occupation to be central in university curriculum is not only being examined in Australia, with educators from the United States also investigating and developing an increased focus on occupation in curricula (Hooper et al ., ).…”
Section: Discussionsupporting
confidence: 82%
“…Fortune and Kennedy‐Jones’ () opinion piece identified occupation as the primary threshold concept for occupational therapy. Rodger and Turpin () also identified purposeful and meaningful occupation as a threshold concept, supporting the finding in this study that occupation is a threshold concept in the discipline.…”
Section: Discussionmentioning
confidence: 99%
“…They identified the threshold concepts, purposeful and meaningful occupation, client centred practice, integral nature of occupational therapy theory and practice, identity as an occupational therapist and thinking critically, reasoning and reflecting . In a recent theoretical review, Australian researchers Fortune and Kennedy‐Jones () fore‐grounded the threshold concept characteristic of boundedness and proposed occupation and its relationship with health as the ‘primary threshold concept for occupational therapy’ (p. 5). The perspectives of the authors of this study will be presented in the discussion section of this article.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the literature describing threshold concepts of student learning has explored the benefits of examining what and how educators teach (Rodger et al, 2015). It is clear that educators are committed to improving and strengthening the scholarship of occupational therapy education (Fortune & Kennedy-Jones, 2014;Nicola-Richmond, Pepin & Larkin, 2016;Rodger et al;Towns & Ashby, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Literature has instead explored mechanisms of teaching such as utilising models of practice (Ashby & Chandler, 2010;Towns & Ashby, 2014); the means by which occupation and occupation-centred approaches can be introduced into curriculum (Hooper et al, 2015;Krishnagiri, Hooper, Price, Taff & Bilics, 2017;Pierce, 1999) and how teaching an occupational perspective can enhance specific areas of practice such as work rehabilitation (Burwash, 1999). Increasingly research papers, commentaries and viewpoints which consider occupation in curriculum design and as a threshold concept have featured in the Australian literature or been written by Australian academics (Fortune & Kennedy-Jones, 2014;Rodger, Turpin & O'Brien, 2015;Tanner, 2011). A 2016 study found that occupational therapy graduates lacked confidence, and in some cases, were unwilling to implement occupation-based approaches in practice (Di Tommaso, Isbel, Scarvell & Wicks, 2016).…”
Section: Introductionmentioning
confidence: 99%